1996
DOI: 10.1097/00006123-199605000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical Management of Thoracic and Lumbar Vertebral Osteomyelitis and Discitis in Adults: A Review of 43 Consecutive Surgically Treated Patients

Abstract: We report 43 consecutive surgically treated patients with pyogenic (37 patients) and tuberculous (6 patients) osteomyelitis of the thoracic and lumbar spine encountered within an 8-year period, including 1 with late recurrence after 15 months. There were 24 men and 18 women, ranging in age from 21 to 83 years. Twenty-six patients were in poor general condition because of associated illnesses, especially diabetes mellitus. Disease occurred at the thoracic level in 19 patients and on the lumbar spine in 24. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
118
1
13

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(141 citation statements)
references
References 26 publications
9
118
1
13
Order By: Relevance
“…(1) Debridement, spinal cord decompression, correction of deformities, bone grafting, and internal fixation can be completed in one incision and surgical position and iatrogenic spinal injury avoided while turning over, which is similar to the best results obtained via anterior decompression [21,22]. (2) Without one-lung ventilation, the interference of pulmonary function is relatively small, and there are fewer postoperative complications such as atelectasis, lung infection, and chylothorax because of fewer traumas.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Debridement, spinal cord decompression, correction of deformities, bone grafting, and internal fixation can be completed in one incision and surgical position and iatrogenic spinal injury avoided while turning over, which is similar to the best results obtained via anterior decompression [21,22]. (2) Without one-lung ventilation, the interference of pulmonary function is relatively small, and there are fewer postoperative complications such as atelectasis, lung infection, and chylothorax because of fewer traumas.…”
Section: Discussionmentioning
confidence: 99%
“…The reported techniques of surgical treatment range from anterior debridement and interbody fusion [13], debridement and internal fixation from the posterior approach [17] to combined single-stage or twostage posterior instrumentation with anterior debridement and bone grafting [1,5,7,8,11,14,15,19]. Anterior instrumentation or the use of cages has been anecdotally reported, but there is a critical discussion concerning the role of spinal implants in the presence of infection [4,8,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, in most patients, the ESR drops to less than half of the original value at the completion of antibiotic therapy. Although it has not often been described in literature, Rath et al [7] reported that elevation of the CRP is a more accurate finding in vertebral osteomyelitis. The CRP is also a more constant laboratory finding than ESR and it starts to drop earlier after antibiotherapy according to our experience.…”
Section: Discussionmentioning
confidence: 98%
“…But the symptoms and signs were not affected, and the ESR and CRP did not drop in spite of the quartet chemotherapy, and the lesion was operated because of huge prevertebral abscess causing disphagia. It is reported that ESR is a useful guide in evaluating response to therapy during the course of the disease in vertebral osteomyelitis [7]. However, in most patients, the ESR drops to less than half of the original value at the completion of antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation